REVOLUSI YAYASAN SOSIAL DAN KEMANUSIAAN TERINTEGRASI BAGI ANAK JALANAN DAN YATIM PIATU DALAM NILAI-NILAI ISLAM - Imamul Arifin; Andika Adinul Yahya; Muhammad Thoriq Azzam (Profetika: Jurnal Studi Islam, 2020)
The Revolution of Human Resources (SDA) and Mental Nation is indeed important today to sustain the progress of the nation. But before that, it must be realized about the lack of attention to education for people who are not addressed, for example street children and orphans in need. All elements of the nation should be realize of the deficiency or something that needs to be improved from this. The government, educational institutions and humanitarian social bodies that form the nation’s generation are very important for this. But here, it is emphasized for the Social Foundation and humanity to be more able to pay attention to their future needs for the better, because this institution is a suitable place for them to get quality education, character, and morals that are in accordance with Islamic values, where the aim is to provide equitable justice for the people’s and make a better national life.